2024
DOI: 10.1001/jamaneurol.2024.0017
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Cerebrospinal Fluid Biomarkers of Disease Activity and Progression in Multiple Sclerosis

Anne H. Cross,
Jeffrey M. Gelfand,
Simon Thebault
et al.

Abstract: ImportanceBiomarkers distinguishing nonrelapsing progressive disease biology from relapsing biology in multiple sclerosis (MS) are lacking. Cerebrospinal fluid (CSF) is an accessible fluid that most closely reflects central nervous system biology.ObjectiveTo identify CSF biological measures associated with progressive MS pathobiology.Design, Setting, and ParticipantsThis cohort study assessed data from 2 prospective MS cohorts: a test cohort provided serial CSF, clinical, and imaging assessments in a multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…However, after adjusting our analysis for relevant MRI activity three months apart from the PIRA event (PIRMA), CSF GFAP was indeed independently associated with PIRMA. This finding is in line with a number of previous studies [ 12 , 41 , 42 ]. GFAP is the predominant intermediate filament protein within astrocytes.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, after adjusting our analysis for relevant MRI activity three months apart from the PIRA event (PIRMA), CSF GFAP was indeed independently associated with PIRMA. This finding is in line with a number of previous studies [ 12 , 41 , 42 ]. GFAP is the predominant intermediate filament protein within astrocytes.…”
Section: Discussionsupporting
confidence: 94%
“…After the development of an in-house method to measure GFAP in CSF [ 30 ], we demonstrated for the first time an association between CSF GFAP and disease progression in MS [ 12 ]. Further, a very recent study demonstrated a strong association between CSF GFAP and nonrelapsing progressive MS biology [ 42 ]. In that study, CSF GFAP was found to correlate with slowly expanding lesions (SELs), higher EDSS scores and lower thalamic volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, this altered phenotype favors accumulation of those myeloid cells in the CSF. In line with our data, studies have demonstrated that B cell depletion by aCD20 mAbs like rituximab and ocrelizumab in MS patients led to a strong reduction of CSF B cells and, to a lesser degree, T cells ( 48 50 ). To our knowledge, no data regarding CSF macrophages in B cell depleted CSF has been published.…”
Section: Discussionsupporting
confidence: 92%
“…CHI3LI is associated with increased clinical severity and spinal cord volume loss [ 45 , 49 ]. The presence of reactive astrocytes, which are incompletely reflected by glial fibrillary acidic protein (GFAP) expression, are a pathological hallmark of MS. Clinically, CSF and serum GFAP levels correlate modestly with progression, independent of relapse activity [ 47 , 50 ]. We would seek to include an assessment of axonal injury and astrocyte reactivity in future DP studies.…”
Section: Discussionmentioning
confidence: 99%